Leverage Shocks : Firm-Level Evidence on Debt Overhang and Investment - Cevik, Serhan (IMF Working Papers; Working Paper ;, 2020)
The global economy is in the midst of an unprecedented slump caused by the coronavirus pandemic. This systemic risk like no other at a time of record-breaking debt levels, especially among nonfinancial firms across the world, could exacerbate corporate vulnerabilities, deepen macro-financial instability, and cause long-lasting damage to economic potential. Using data on more than 2.8 million nonfinancial firms from 52 countries during the period 1997-2018, we develop a two-pronged approach to investigate the relationship between corporate leverage and fixed investment spending. The empirical analysis, robust to a battery of sensitivity checks, confirm corporate leverage is highly vulnerable to disruptions in profitability and cash flow at the firm level and economic growth at the aggregate level. These findings imply that corporate debt overhang could become a strenuous burden on nonfinancial firms, especially if the COVID-19 pandemic lingers and global downturn becomes protracted.